Carbon aerogel supported platinum catalysts for selective hydrogenation of cinnamaldehyde - Machado, Bruno (2010)
This paper describes the preparation and characterization of 1% wt. Pt catalysts supported in carbon aerogels for the application in the liquid-phase selective hydrogenation of cinnamaldehyde. Carbon aerogel supports with different textures were activated with hydrogen peroxide and ammonium peroxydisulfate leading to large amounts of surface groups but keeping unchanged their textural properties. After introducing Pt, the surface chemistry and morphology of the catalysts was characterized by analytical techniques like SEM, TPD, N2 adsorption isotherms, mercury porosimetry and H2 chemisorption. Catalysts prepared with activated aerogels exhibited good selectivity towards the desired product, cinnamyl alcohol. A high temperature post-treatment of the catalysts failed to enhance their selectivity, mainly leading to hydrocinnamaldehyde production.